Pengaruh Kemudahan Persepsi Serta Kualitas Informasi Terhadap Minat Mahasiswa Jurusan Perbankan Syariah Dalam Penggunaan Layanan M-Banking Di Bank Syariah Indonesia - M. Yoga Pratama Harahap; Muhammad Irwan Padli Nasution; Sri Suci Ayu Sundari (Islamic Education Journal, 2022)
The presence of mobile banking can also have a positive impact because the main goal of mobile banking is to make it easier for students to make every transaction they want to make. The purpose of this study was to determine the effect of efficiency, security, and convenience on students' interest in transacting using mobile banking among Islamic bank students. Banking services have shown increasing progress recently, starting with internet banking which can provide convenience in banking transactions. After that, the SMS-based mobile banking (M-Banking) service, known as SMS bank, was born. This sms banking service makes it easier for customers to carry out banking transactions such as balance checks, account transfers and others.